Antidiabetic Activities and Phytochemical Screening of Broccoli Plants (Brassica oleracea L. var. italica) - Chairunnisa, Alya; Haryoto, Haryoto; Abdul, Ahwan (Universitas Muhammadiyah Surakarta, 2024)
Diabetes mellitus is a metabolic disease that is characterized by hyperglycemia which is closely related to pancreatic β cell dysfunction and insulin resistance. Brassica oleracea L. var. italica is a member of the Brassicaceae family which has antidiabetic properties. These effects are caused by the presence of various phytochemical compounds in broccoli plants, flavonoids, tannins, saponins, alkaloids, steroids, glucosinolates, isothiocyanates, and phenolics. The aim of this review is to find out the antidiabetic activity of broccoli plants and the mechanism of action of phytochemical compounds in broccoli plants that support these benefits. The preparation of this review was sourced from articles obtained from the PubMed and Google Scholar databases with the interval 2012-2021 publication year. Based on the selected articles, it shows that the content of phytochemical compounds in broccoli plants has an effect on reducing blood sugar levels through various mechanisms. Therefore, the results of this study are expected to be used as support for the use of broccoli plants as antidiabetic agents.